The role of diet in the prevention of migraine attacks - O. O. Kopchak; O. Ye. Hrytsenko (Zaporožskij Medicinskij Žurnal)
The review provides information concerning the influence of dietary factors and different types of diet on the origin and frequency of migraine headaches according to the up-to-date scientific data. The relevance of the problem is associated with high prevalence of migraine, which is a common cause of disability amongst young people. Gut – brain axis takes a significant place in the pathophysiology of migraine. The concept of a gut-brain axis explains a bidirectional relationship between the gastrointestinal system and the central nervous system. It has been suggested that changes in the gut-brain axis functioning may play a role in the pathogenesis of migraine. The review describes possible mechanisms of gut microbiota involvement in the pathogenesis of migraine.